Soft magnetic alloys and magnetic components.
The soft magnetic alloy with a P-enriched surface and optional Co-enriched region addresses the corrosion issues of existing alloys, enhancing corrosion resistance and maintaining high magnetic performance.
Patent Information
- Application Number
- JP2021061027
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-03-31
AI Technical Summary
Soft magnetic alloys used in magnetic components are prone to corrosion, such as rust, depending on storage conditions and use environments, necessitating improved corrosion resistance.
A soft magnetic alloy with a composition containing Fe and P, featuring a P-enriched region on its surface with a higher P concentration than the internal region, and optionally a Co-enriched region overlapping with the P-enriched region, to enhance corrosion resistance.
The described soft magnetic alloy effectively suppresses rust during flooding and improves corrosion resistance, maintaining high saturation magnetic flux density while ensuring durability.
Smart Images

Figure 0007658781000011 
Figure 0007658781000012 
Figure 0007658781000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a soft magnetic alloy and a magnetic part using the soft magnetic alloy. [Background technology]
[0002] Soft magnetic alloys such as those shown in Patent Documents 1 to 3 are known as magnetic materials used in various magnetic parts such as inductors. These soft magnetic alloys have a higher saturation magnetic flux density Bs than ferrite materials and have good soft magnetic properties. However, soft magnetic alloys may become corroded, such as rusting, depending on the storage conditions and usage environment, so there is a demand for improved corrosion resistance. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-293099 A [Patent Document 2] JP 2007-231415 A [Patent Document 3] JP 2014-167139 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a soft magnetic alloy having high corrosion resistance, and a magnetic component using the soft magnetic alloy. [Means for solving the problem]
[0005] In order to achieve the above object, the soft magnetic alloy according to the present invention comprises: an inner region having a soft magnetic alloy composition including Fe and P (phosphorus); and a P-enriched region that is located closer to the surface than the internal region and has a higher P concentration than the internal region.
[0006] As a result of extensive research, the present inventors have found that a soft magnetic alloy having the above-mentioned characteristics suppresses rusting when immersed in water and improves corrosion resistance.
[0007] Preferably, the P-enriched region is composed of elements common to the internal region, The total content of elements in the P-enriched region that are common to the internal region is 50% or more in terms of substance amount ratio.
[0008] Preferably, the internal region contains Co, a Co-enriched region is present closer to the surface than the internal region, and the Co-enriched region overlaps with at least a portion of the P-enriched region. The Co-enriched region is preferably a metallic phase, and a degree of Co enrichment in the Co-enriched region is preferably greater than 1.2.
[0009] Also, the degree of P concentration in the P-enriched region is preferably 1.5 or more, and more preferably 2.0 or more.
[0010] Preferably, the soft magnetic alloy has an amorphous degree of 85% or more.
[0011] The soft magnetic alloy may be in the form of a thin ribbon or a powder.
[0012] The application of the soft magnetic alloy of the present invention is not particularly limited, and it can be applied to various magnetic parts such as coil parts such as inductors, filters, antennas, etc. Among the above applications, the soft magnetic alloy of the present invention is suitable as a material for the magnetic core in coil parts and the like. [Brief description of the drawings]
[0013] [Figure 1A] FIG. 1A is an enlarged cross-sectional view of a main part of a soft magnetic alloy 1 according to one embodiment of the present invention. [Figure 1B] FIG. 1B is an example of an enlarged cross-sectional view of a main part of a soft magnetic alloy 1a according to one embodiment of the present invention. [Figure 2A] FIG. 2A is an example of a chart obtained by X-ray crystal structure analysis. [Figure 2B] FIG. 2B is an example of a pattern obtained by profile fitting the chart shown in FIG. 2A. [Figure 3A] FIG. 3A is an example of a graph obtained by performing a line analysis using EDX along the measurement line LM shown in FIG. 1A. [Figure 3B] FIG. 3B is an example of a graph obtained by performing a line analysis using EDX along the measurement line LMa shown in FIG. 1B. [Figure 4A] FIG. 4A is a cross-sectional view showing a soft magnetic alloy 1b according to one embodiment of the present invention. [Figure 4B] FIG. 4B is an enlarged cross-sectional view of region IVB shown in FIG. 4A. [Figure 5A] FIG. 5A is an example of an EELS image of the soft magnetic alloy 1 shown in FIG. 1A. [Figure 5B] FIG. 5B is an example of an EELS image of the soft magnetic alloy 1a shown in FIG. 1B. [Figure 5C] FIG. 5C is an example of a STEM image of the soft magnetic alloy 1b shown in FIG. 4A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the present invention will be described in detail based on the embodiments shown in the drawings.
[0015] The soft magnetic alloy 1 of the present embodiment may have a ribbon shape, a powder shape, or other block shape, and the shape of the soft magnetic alloy 1 is not particularly limited. The dimensions of the soft magnetic alloy 1 are also not particularly limited. For example, when the soft magnetic alloy 1 is in a ribbon shape, the thickness of the ribbon may be 15 μm to 100 μm, and when the soft magnetic alloy 1 is in a powder shape, the average particle size of the soft magnetic alloy powder may be 0.5 μm to 150 μm, and is preferably 0.5 μm to 25 μm.
[0016] The above average particle size can be measured by various particle size analysis methods such as laser diffraction, but it is preferable to measure it using a particle image analyzer Morphologi G3 (manufactured by Malvern Panatical). In Morphologi G3, soft magnetic alloy powder is dispersed by air, the projected area of the particles constituting the powder is measured, and the particle size distribution based on the circular equivalent diameter is obtained from the projected area. Then, in the obtained particle size distribution, the particle size at which the cumulative relative frequency based on volume or number is 50% can be calculated as the average particle size. When soft magnetic alloy 1 is included in a magnetic core, the average particle size of soft magnetic alloy 1 (powder) can be calculated by measuring the circular equivalent diameter of the particles included in the cross section by observing the cross section using an electron microscope (SEM, STEM, etc.).
[0017] Fig. 1A is an enlarged cross-sectional view of the vicinity of the surface of the soft magnetic alloy 1. As shown in Fig. 1A, the soft magnetic alloy 1 has an internal region 2 and a concentrated portion 11 located on the surface side of the soft magnetic alloy 1 relative to the internal region 2. In this embodiment, the "inner side" refers to a side closer to the center of the soft magnetic alloy 1, and the "surface side" or "outer side" refers to a side farther from the center of the soft magnetic alloy 1.
[0018] (internal area 2) The internal region 2 is a base portion of the soft magnetic alloy 1 that occupies at least 90 vol % or more of the volume of the soft magnetic alloy 1. Therefore, the average composition of the soft magnetic alloy 1 can be regarded as the composition of the internal region 2, and the crystal structure of the soft magnetic alloy 1 can be regarded as the crystal structure of the internal region 2. The volume ratio of the internal region 2 described above can be replaced with an area ratio, and the internal region 2 occupies at least 90% or more of the cross-sectional area of the soft magnetic alloy 1.
[0019] The inner region 2 (i.e., soft magnetic alloy 1) has a soft magnetic alloy composition containing Fe and P (phosphorus), and the P content in the inner region 2 is preferably 0.1 at% to 10 at%, and more preferably 2.0 at% to 7.0 at%. Furthermore, the inner region 2 preferably contains Co in addition to Fe and P.
[0020] The specific alloy type of the inner region 2 is not particularly limited, and may be, for example, a crystalline soft magnetic alloy containing P, such as an Fe-Co based alloy, an Fe-Co-V based alloy, an Fe-Co-Si based alloy, an Fe-Co-Si-Al based alloy, or an Fe-Co-Si-Cr based alloy. From the viewpoint of reducing the coercive force, the inner region 2 preferably has an amorphous or nanocrystalline alloy composition, and examples of the amorphous or nanocrystalline soft magnetic alloy include an Fe-Co-PC based alloy, an Fe-Co-BP based alloy, or an Fe-Co-B-Si-P based alloy. More specifically, the inner region 2 is an alloy having a composition formula ((Fe (1-(α+β) Co α Ni β ) 1-γ X1 γ ) (1-(a+b+c+d+e)) B a P b S c C d Cr e It is more preferable that the alloy has a composition that satisfies the above formula, and by having the above formula, an amorphous, heteroamorphous, or nanocrystalline crystal structure is easily obtained.
[0021] In the above composition formula, B is boron, P is phosphorus, C is carbon, and X1 is one or more elements selected from Ti, Zr, Hf, Nb, Ta, Mo, W, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, O, Au, Cu, rare earth elements, and platinum group elements. Rare earth elements include Sc, Y, and lanthanides, and platinum group elements include Ru, Rh, Pd, Os, Ir, and Pt. In addition, α, β, γ, a, b, c, d, and e are atomic ratios, and these atomic ratios preferably satisfy the following requirements.
[0022] The content (α) of Co relative to Fe is 0≦α≦0.700, may be 0.005≦α≦0.600, may be 0.030≦α≦0.600, or may be 0.050≦α≦0.600. When α is within the above range, Bs and corrosion resistance are improved. From the viewpoint of improving Bs, it is preferable that 0.050≦α≦0.500. The larger α is, the more corrosion resistance tends to be improved, but if α is too large, Bs is likely to decrease.
[0023] The content (β) of Ni relative to Fe is 0≦β≦0.200. That is, Ni may not be contained, or may be 0.005≦β≦0.200. From the viewpoint of improving Bs, it may be 0≦β≦0.050, 0.001≦β≦0.050, or 0.005≦β≦0.010. The larger β is, the more the corrosion resistance tends to improve, but if β is too large, Bs decreases.
[0024] X1 may be contained as an impurity or may be added intentionally. The content of X1 (γ) is 0≦γ<0.030. That is, less than 3.0% of the total content of Fe, Co and Ni may be substituted with X1.
[0025] Furthermore, when the sum of the atomic ratios of the elements constituting the soft magnetic alloy is 1, the atomic ratio (1-(a+b+c+d+e)) of the total content of Fe, Co, Ni, and X1 is preferably 0.720≦(1-(a+b+c+d+e))≦0.950, and more preferably 0.780≦(1-(a+b+c+d+e))≦0.890. By satisfying this requirement, Bs is easily improved. In addition, by satisfying 0.720≦(1-(a+b+c+d+e))≦0.890, it is easy to obtain an amorphous structure.
[0026] a is the atomic ratio of B, and is preferably 0≦a≦0.200, and from the viewpoint of improving Bs, more preferably 0≦a≦0.150.
[0027] b is the atomic ratio of P, and is preferably 0.001≦b≦0.100, and from the viewpoint of simultaneously improving Bs and corrosion resistance, it is more preferable that 0.005≦b≦0.080, and further more preferably that 0.005≦b≦0.050.
[0028] c is the atomic ratio of Si, and is preferably 0≦c≦0.150. That is, Si does not have to be contained, and from the viewpoint of simultaneously improving Bs and corrosion resistance, it is more preferable that 0.001≦b≦0.070.
[0029] d is the atomic ratio of C, and is preferably 0≦d≦0.050. In other words, C does not have to be contained, and from the viewpoint of simultaneously improving Bs and corrosion resistance, it is more preferable that 0≦d≦0.020.
[0030] e is the atomic ratio of Cr, and is preferably 0≦e≦0.050. That is, from the viewpoint of improving Bs, Cr does not have to be contained, and from the viewpoint of improving both Bs and corrosion resistance, it is more preferable that 0.001≦d≦0.020.
[0031] The composition of the inner region 2 (i.e., the composition of the soft magnetic alloy 1) can be analyzed, for example, by inductively coupled plasma emission spectrometry (ICP). In this case, if it is difficult to determine the amount of oxygen by ICP, impulse heating melting extraction method can be used in combination. In addition, if it is difficult to determine the amount of carbon and sulfur by ICP, infrared absorption method can be used in combination.
[0032] In addition to ICP, composition analysis may be performed using EDX (energy dispersive X-ray analysis) or EPMA (electron probe microanalyzer) attached to an electron microscope. For example, for the soft magnetic alloy 1 contained in a magnetic core having a resin component, composition analysis using ICP may be difficult. In this case, composition analysis may be performed using EDX or EPMA. In addition, if detailed composition analysis is difficult using any of the above methods, composition analysis may be performed using 3DAP (three-dimensional atom probe). When 3DAP is used, the composition of the soft magnetic alloy 1, that is, the inner region 2, can be measured while excluding the effects of resin components and surface oxidation in the analyzed region. This is because 3DAP allows the average composition to be measured by setting a small region (for example, a region of Φ20 nm × 100 nm) inside the soft magnetic alloy 1.
[0033] When a line analysis is performed on a cross section near the surface of the soft magnetic alloy 1 using EDX or EELS (electron energy loss spectroscopy), the internal region 2 can be recognized as a region where the Fe concentration and Co concentration are stable (see FIG. 3A). For example, the average composition obtained by mapping analysis in the internal region 2 can be regarded as the composition of the soft magnetic alloy 1. In this case, the mapping analysis is performed using EDX or EELS, and the measurement location is a region 100 nm or more away from the surface of the soft magnetic alloy 1 in the depth direction (corresponding to the internal region 2), and the measurement field of view may be a range of about 256 nm × 256 nm.
[0034] The crystal structure of the inner region 2 (i.e., the crystal structure of the soft magnetic alloy 1) can be crystalline, nanocrystalline, or amorphous, and is more preferably amorphous. In other words, the degree of amorphization X of the inner region 2 (i.e., the degree of amorphization X of the soft magnetic alloy 1) is preferably 85% or more. A crystal structure with a degree of amorphization X of 85% or more is a structure that is mostly composed of amorphous material, or a structure that is composed of heteroamorphous material. Here, a structure that is composed of heteroamorphous material means a structure in which a small amount of crystals are present in the amorphous material. That is, in this embodiment, the "amorphous crystal structure" means a crystal structure with a degree of amorphization X of 85% or more, which may contain crystals within a range that satisfies the degree of amorphization X.
[0035] In the case of a heteroamorphous structure, the average crystal grain size of the crystals present in the amorphous material is preferably 0.1 nm or more and 10 nm or less. In the present embodiment, the term "nanocrystal" refers to a crystal structure in which the degree of amorphousness X is less than 85% and the average crystal grain size is 100 nm or less (preferably 3 nm to 50 nm), and the term "crystalline" refers to a crystal structure in which the degree of amorphousness X is less than 85% and the average crystal grain size exceeds 100 nm.
[0036] The degree of amorphization X can be measured by X-ray crystal structure analysis using XRD. Specifically, the soft magnetic alloy 1 according to this embodiment is subjected to 2θ / θ measurement by XRD to obtain a chart as shown in Fig. 2A. In this case, the measurement range of the diffraction angle 2θ is set to a range in which a halo derived from the amorphous phase can be confirmed, and is preferably set to, for example, a range of 2θ=30° to 60°.
[0037] Next, profile fitting is performed on the chart shown in Fig. 2A using the Lorentz function shown in the following formula (2). In this profile fitting, it is preferable to set the error between the integrated intensity actually measured by XRD and the integrated intensity calculated using the Lorentz function to within 1%. By this profile fitting, a crystalline component pattern α showing the crystalline scattering integrated intensity Ic as shown in Fig. 2B is obtained. c, amorphous component pattern α showing amorphous scattering integrated intensity Ia a , and the combined pattern α c+a The degree of amorphism X can be calculated by introducing the crystalline scattering integrated intensity Ic and the amorphous scattering integrated intensity Ia obtained here into the following formula (1).
[0038] X = 100 - (Ic / (Ic + Ia) × 100) ... (1) Ic: Crystalline scattering integrated intensity Ia: Amorphous scattering integrated intensity
number
[0039] The method for measuring the degree of amorphousness X is not limited to the above-mentioned method using XRD, and it may be measured by EBSD (crystal orientation analysis) or electron beam diffraction.
[0040] (Concentrated part 11) The concentrated portion 11 contains constituent elements common to the inner region 2, such as Fe, P, and Co, and the total content of the constituent elements common to the inner region 2 in the concentrated portion 11 is 50% or more, preferably 80% or more, calculated as a substance amount ratio. That is, the concentrated portion 11 in this embodiment is not a coating formed by phosphating or the like, but is preferably a phase of a composition consisting of Fe, P, Co, and the like, and is an amorphous metal phase continuous from the inner region 2.
[0041] As described above, the enriched portion 11 is composed of elements common to the inner region 2, but the composition ratio is different between the inner region 2 and the enriched portion 11. Specifically, P is more enriched in the enriched portion 11 than in the inner region 2. In other words, the enriched portion 11 has a P-enriched region 11a in which the P concentration is higher than in the inner region 2 described above, and this P-enriched region 11a covers at least a part of the outer periphery of the inner region 2. In a cross section of the soft magnetic alloy 1, the coverage of the enriched portion 11 (i.e., the P-enriched region 11a) with respect to the inner region 2 is not particularly limited, but can be, for example, 50% or more, and more preferably 80% or more.
[0042] Moreover, it is preferable that Co is more concentrated in the concentrated portion 11 than in the internal region 2, and it is preferable that a Co-enriched region 11b is present in the concentrated portion 11. This Co-enriched region 11b is present overlapping with the P-enriched region 11a in the depth direction (thickness direction) of the soft magnetic alloy 1 from the surface side toward the inside. The degree of overlap between the Co-enriched region 11b and the P-enriched region 11a in the depth direction may be partial or complete, and in the case of partial overlap, it is preferable that the P-enriched region 11a is located closer to the surface of the concentrated portion 11 than the Co-enriched region 11b.
[0043] The concentrated portion 11 having the above-mentioned characteristics can be analyzed by EDX, EELS (electron energy loss spectroscopy), or the like, and is preferably analyzed by EELS, which has a particularly high spatial resolution.
[0044] For example, the presence or absence of the enriched portion 11 and its coverage can be confirmed by observing a cross section near the surface of the soft magnetic alloy 1 with a STEM (scanning transmission electron microscope) or a TEM (transmission electron microscope) and performing a mapping analysis using EDX or EELS. The image (EELS image) shown in FIG. 5A is an example of a mapping analysis result by EELS. Both of the two EELS images in FIG. 5A are the results of measuring the same location, with the EELS image (PL) on the left showing the distribution of P and the EELS image (Co-L) on the right showing the distribution of Co. In the EELS image, the inner region 2 can be recognized as a region where there is almost no shading in the concentration distribution of Co. In the EELS image for P, the contrast is bright at the edge of the inner region 2, and it can be seen that the P concentration is higher than that of the inner region 2. This region with high P concentration is the P enriched region 11a.
[0045] In the EELS image of Co, the contrast indicating Co is bright at the edge of the internal region 2, and it is found that the Co concentration is higher than in the internal region 2. This region with high Co concentration is the Co-enriched region 11b, and it can be seen in FIG. 5A that the P-enriched region 11a and the Co-enriched region 11b overlap each other.
[0046] The average thickness t1a of the P-enriched region 11a determined by the mapping analysis is preferably 0.3 nm or more. The upper limit of t1a is not particularly limited and can be, for example, 30 nm or less. By increasing t1a within this preferred range, better results can be obtained in terms of corrosion resistance. Note that the average thickness t1a is preferably calculated by measuring the thickness of the P-enriched region 11 at at least three or more points by changing the measurement field of view.
[0047] The average thickness t1b of the Co-enriched region 11b can be in the same range as t1a, and may be t1a>t1b or t1a≦t1b. The thickness t1 of the enriched portion 11 is the thickness of a region where the detection intensity of P and / or Co is high, and when the Co-enriched region 11b does not exist, t1=t1a. When the P-enriched region 11a and the Co-enriched region 11b completely overlap, t1=t1a (when t1a>t1b) or t1=t1b (when t1a≦t1b).
[0048] As described above, the P-enriched region 11a and the Co-enriched region 11b may be extremely thin, and therefore, when identifying the P-enriched region 11a and the Co-enriched region 11b, it is preferable to use not only mapping analysis but also line analysis. M 3A is a schematic diagram illustrating the results of line analysis along the line 11, where the vertical axis indicates the detection intensity of each element (i.e., the intensity of characteristic X-rays) and the horizontal axis indicates the distance (depth) from the outermost surface 10. As shown in FIG. 3A, in the line analysis results, a peak where the P concentration is high can be confirmed at the edge of the internal region 2 where the concentrations of Fe and Co are stable, and the location where this P peak exists is the P-enriched region 11a. In other words, in the P-enriched region 11a, a maximum value of the P concentration exists, and the presence or absence of the above-mentioned peak can be used to confirm the presence or absence of the P-enriched region 11a. Note that, when the Co-enriched region 11b exists, it can be confirmed that a Co peak exists so as to overlap with the P peak, as shown in FIG. 3A.
[0049] As described above, the enriched portion 11 is preferably a metal phase, and the phase state of the enriched portion 11 can be confirmed, for example, by the above-mentioned line analysis, mapping analysis, or analysis using an EELS detector associated with a STEM or TEM. For example, by analyzing a spectrum obtained by EELS, the ratio of oxide Co and metal Co in the Co enriched region 11 can be calculated, and if the ratio of metal Co is higher than that of oxide Co, the Co enriched region 11 is defined as a metal phase. Also, if an oxide layer (such as the SB oxide layer 12, Fe oxide layer 13, and coating layer 20 described later) exists outside the enriched portion 11, the detection intensity of oxygen in the enriched portion 11 will be lower than that of the oxide layer in mapping analysis or line analysis. Such analysis reveals that the enriched portion 11 is a metal phase.
[0050] For the P-enriched region 11a, the degree of P enrichment is expressed by the intensity ratio, and this intensity ratio is calculated by line analysis using EDX or EELS. P The detection intensity of P in the P-enriched region 11a is C11 P As, C11 P / C2 P is the P intensity ratio (degree of concentration) in the P-enriched region 11a. This P intensity ratio is preferably 1.3 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. The upper limit of the degree of P concentration is not particularly limited, and can be, for example, 20 or less.
[0051] On the other hand, the degree of Co enrichment in the Co-enriched region 11b is determined by the Co substance ratio (C2 Co ) to the Co-enriched region 11b (C11 Co ) ratio (C11 Co / C2 Co) The degree of Co enrichment is preferably more than 1.02, and more preferably more than 1.20. The upper limit of the degree of Co enrichment is not particularly limited, and can be, for example, 20 or less. If a soft magnetic alloy consisting of an internal region 2 in which no enriched portion 11 is formed is taken as a reference alloy, the corrosion resistance of the soft magnetic alloy 1 of this embodiment relative to the reference alloy tends to be improved as the degree of Co enrichment is higher.
[0052] C2 used to calculate Co concentration Co and C11 Co is measured by component analysis using EELS. Co is the ratio of the amount of Co to the total amount of Fe and Co detected in the inner region 2, and is calculated by analyzing the EELS spectrum. Co is the ratio of the amount of Co to the total amount of Fe and Co detected in the Co-enriched region 11b. That is, the ratio of the amount of Co in each region is expressed as Co / (Fe+Co), and the denominator is (Fe+Co) to eliminate the influence of impurities (such as elements mixed in during the preparation of the measurement sample).
[0053] In addition, the resolution in this analysis is preferably set to 0.5 nm or less, and C2 Co is preferably measured at a depth of 0.2 μm or more from the outermost surface 10 of the soft magnetic alloy 1 toward the inside. The P intensity ratio and the Co concentration are preferably calculated as an average value by performing the above measurements in at least five or more visual fields.
[0054] As described above, the soft magnetic alloy 1 has a characteristic surface layer structure (enriched portion 11) including a P-enriched region 11a and a Co-enriched region 11b. In particular, in this embodiment, as shown in Fig. 1A and Fig. 3A, the P-enriched region 11a is located on the outermost surface side and constitutes the outermost surface 10 of the soft magnetic alloy 1. However, other surface layer structures may be present outside the P-enriched region 11a.
[0055] 1B, an Sb-oxide layer 12 containing Si and / or B may be formed to cover the surface side of the P-enriched region 11a. The Sb-oxide layer 12 is a region in which the concentration of at least one element selected from Si and B is higher than that of the inner region 2, and either Si or B, or both Si and B, are enriched.
[0056] In fact, Fig. 5B is an example of an EELS image of the soft magnetic alloy 1a shown in Fig. 1B, and all four EELS images shown in Fig. 5B are the results of measuring the same location. In the EELS image of B in Fig. 5B (top right: BK), the contrast is brighter on the surface side than the enriched portion 11 where P and Co are enriched, and it can be confirmed that the concentration of B in this location is higher than that of the internal region 2 and the enriched portion 11. In the case of Fig. 5B, this region with a high B concentration is the Sb oxide layer 12.
[0057] When the internal region 2 contains Si and / or B, the SB oxide layer 12 may be generated during the formation of the enriched portion 11, and is preferably an amorphous oxide phase. Furthermore, the average thickness t2 of the SB oxide layer 12 is preferably 0.5 nm or more. The upper limit of t2 is not particularly limited, and can be, for example, 30 nm or less.
[0058] In addition, an Fe oxide layer 13 containing Fe may be formed outside the P-enriched region 11a. This Fe oxide layer 13 may be formed together with the enriched region 11 in the process of forming the enriched region 11, and the Fe concentration in the Fe oxide layer 13 is higher than that in the enriched region 11 and the internal region 2. As shown in FIG. 1B, when the SB oxide layer 12 is present, the Fe oxide layer 13 is preferably located closer to the surface than the SB oxide layer 12, and further preferably has a higher crystallization area ratio than the SB oxide layer 12.
[0059] In fact, in the EELS image of Fe in FIG. 5B (lower right side: Fe-L), the contrast is brighter on the surface side than the SB oxide layer 12, and it can be confirmed that there is a region with high Fe concentration on the outermost surface of the soft magnetic alloy 1a. In FIG. 5B, this region is the Fe oxide layer 13, and the Fe oxide layer 13 constitutes the outermost surface 10 of the soft magnetic alloy 1a. In this embodiment, the average thickness t3 of the Fe oxide layer 13 is preferably 1 nm or more. The upper limit of t3 is not particularly limited and can be, for example, 50 nm or less.
[0060] FIG. 3B shows the measurement line L M 5A is a graph showing a simulated result of EDX line analysis along a. When the SB oxide layer 12 exists, as shown in FIG. 3B, a peak of Si or / and B is observed on the surface side of the peak of P, and the detection intensity of oxygen is high so as to overlap with the peak of Si or / and B. When the Fe oxide layer 13 exists on the surface side of the SB oxide layer 12, a peak of Fe can be confirmed on the surface side of the peak of Si or / and B. Thus, the presence or absence of the SB oxide layer 12 or the Fe oxide layer 13 can be confirmed by line analysis using EDX or EPMA, and can also be confirmed by mapping analysis as shown in FIG. 5B.
[0061] Also, as in the soft magnetic alloy 1b shown in FIG. 4A and FIG. 4B, an insulating coating layer 20 may be formed on the outside of the P-enriched region 11a. This coating layer 20 is a coating formed by a surface treatment such as coating after forming the enriched portion 11, and its average thickness is preferably 5 nm to 100 nm, more preferably 50 nm or less. In other words, when the coating layer 20 is formed, the outermost surface 10 of the soft magnetic alloy 1b is composed of the coating layer 20 and is located closer to the surface of the soft magnetic alloy 1b than the enriched portion 11, the SB oxide layer 12, and the Fe oxide layer 13. In fact, FIG. 5C is an example of a STEM image of the soft magnetic alloy 1b shown in FIG. 4A. In the STEM image, a bright contrast area can be confirmed on the outermost surface 10 of the soft magnetic alloy 1b, and this area is the coating layer 20.
[0062] Thus, the surface layer structure of the soft magnetic alloy 1 may include other layers (such as the SB oxide layer 12, the Fe oxide layer 13, and the coating layer 20) in addition to the enriched portion 11, but even if other layers are present, the enriched portion 11 is present on the side in contact with the internal region 2. The perpendicular distance d1 (see Figs. 1B and 4B) from the outermost surface to the P enriched region 11a is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. In particular, when the coating layer 20 is not present and the SB oxide layer 12 or the Fe enriched region 13 constitutes the outermost surface 10, the perpendicular distance d1 is preferably 30 nm or less, and more preferably 20 nm or less.
[0063] In addition, it is preferable to prepare a measurement sample for analyzing the enriched portion 11 by a microsampling method using a FIB (focused ion beam). For example, a Pt film is formed by sputtering on the outermost surface 10 of the soft magnetic alloy 1 to a thickness of about 30 nm for surface protection during processing, and then a range of about 2 μm deep from the outermost surface is cut out by FIB to obtain a thin sample. The thin sample is then processed to reduce the thickness in the direction perpendicular to the depth direction to 20 nm or less. This thin sample can be used as a measurement sample for TEM or HRTEM observation.
[0064] A method for producing the soft magnetic alloy 1 according to this embodiment will be described below.
[0065] The base portion (internal region 2) of the soft magnetic alloy 1 can be produced by various melting methods, but is preferably produced by a method of quenching molten metal (molten metal). This is because quenching makes it easier to obtain an amorphous soft magnetic alloy 1. For example, a ribbon-shaped soft magnetic alloy 1 can be produced by a single roll method, and a powder-shaped soft magnetic alloy 1 can be produced by an atomization method. In the following, a method of producing a soft magnetic alloy ribbon by the single roll method and a method of producing a soft magnetic alloy powder by a gas atomization method as an example of an atomization method will be described.
[0066] In the single roll method, first, raw materials (pure metals, etc.) of each element constituting the soft magnetic alloy 1 are prepared and weighed to obtain the desired alloy composition. Then, the raw materials of each element are melted to prepare a master alloy. The melting method for preparing the master alloy is not particularly limited, and may be, for example, a method of melting by high-frequency heating in a chamber with a predetermined degree of vacuum.
[0067] Next, the above-mentioned mother alloy is heated to melt, and a molten metal is obtained. The temperature of the molten metal may be set in consideration of the melting point of the target alloy composition, and may be, for example, 1200 to 1600°C. In the single roll method, the molten metal is supplied to a cooled rotating roll using a nozzle or the like, and a soft magnetic alloy ribbon is produced in the direction of rotation of the roll. At this time, the thickness of the obtained ribbon can be adjusted by controlling the rotation speed of the roll, the gap between the nozzle and the roll, the temperature of the molten metal, and the like. In addition, the temperature and rotation speed of the roll may be set under conditions that make the soft magnetic alloy easily amorphous, and for example, the roll temperature is preferably 20 to 30°C, and the rotation speed is preferably 20 to 30 m / sec. The atmosphere in the chamber is not particularly limited, and may be, for example, an air atmosphere or an inert gas atmosphere.
[0068] In the gas atomization method, molten metal at 1200 to 1600°C is obtained in the same manner as in the single roll method, and then the molten metal is sprayed in a chamber to produce powder. Specifically, the molten metal is discharged from a discharge port toward a cooling section in the chamber, and high-pressure gas is sprayed toward the discharged dripping molten metal. The dripping molten metal is scattered in the chamber by the spray of high-pressure gas, and then collides with the cooling section (cooling water) to be rapidly cooled and solidified, becoming soft magnetic alloy powder. The particle shape of the soft magnetic alloy powder obtained by this gas atomization method is usually spherical, and the average circularity of the soft magnetic alloy powder is preferably 0.8 or more, more preferably 0.9 or more, and even more preferably 0.95 or more.
[0069] As the high pressure gas, it is preferable to use an inert gas such as nitrogen gas, argon gas, or helium gas, or a reducing gas such as an ammonia decomposition gas, and the pressure at which the high pressure gas is injected is preferably 2.0 MPa or more and 10 MPa or less. The amount of molten metal injected is preferably 0.5 kg / min or more and 4.0 kg / min or less. In the gas atomization method, the particle size and shape of the soft magnetic alloy powder can be adjusted by the ratio of the pressure of the high pressure gas to the amount of molten metal injected.
[0070] After obtaining a ribbon or powder of soft magnetic alloy as described above, the soft magnetic alloy is heat-treated at a low temperature in an atmosphere of a certain oxygen concentration under a certain pressure state, thereby forming the concentrated portion 11.
[0071] Specifically, the holding temperature during the heat treatment is preferably a temperature at which the soft magnetic alloy does not crystallize, for example, 200°C to 400°C. The temperature holding time is preferably 0.5 hours to 3.0 hours. The oxygen concentration in the heating furnace is preferably 20 ppm to 2000 ppm, more preferably 100 ppm to 1000 ppm. Furthermore, while controlling the oxygen concentration as described above, the heating furnace is made positive pressure by introducing an inert gas such as argon gas or nitrogen gas, and the gauge pressure in the heating furnace is preferably 0.05 kPa to 0.50 kPa, and more preferably 0.15 kPa to 0.45 kPa when the Co-enriched region 11b is formed. The gauge pressure means the pressure obtained by subtracting the atmospheric pressure from the absolute pressure (pressure when an absolute vacuum is 0 Pa).
[0072] By performing heat treatment under such conditions, a P-enriched region 11a (i.e., enriched portion 11) having a predetermined characteristic is formed on the surface layer side of the soft magnetic alloy 1, and when the soft magnetic alloy 1 contains Co, a Co-enriched region 11a may also be formed. Furthermore, when the soft magnetic alloy 1 contains Si and / or B, the above heat treatment may form an Sb oxide layer 12, and depending on the heat treatment conditions, an Fe oxide layer 13 may be formed. Note that when the soft magnetic alloy 1 is made crystalline or nanocrystalline (i.e., when the degree of amorphization X is less than 85%), a pre-process heat treatment for controlling crystallinity may be performed before performing the heat treatment for forming the enriched portion 11 described above.
[0073] When forming the coating layer 20 as shown in FIG. 4A and FIG. 4B, after forming the concentrated portion 11 by the above-mentioned heat treatment, a coating formation treatment such as phosphate treatment, mechanical alloying method, silane coupling treatment, hydrothermal synthesis, etc. may be performed. The types of the coating layer 20 to be formed include phosphate, silicate, soda-lime glass, borosilicate glass, lead glass, aluminosilicate glass, borate glass, sulfate glass, etc. Examples of the phosphate include magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, cadmium phosphate, etc., and examples of the silicate include sodium silicate, etc. When the coating layer 20 is formed, an improvement in the withstand voltage of the magnetic core including the soft magnetic alloy 1 can be expected.
[0074] The above steps provide a soft magnetic alloy 1 having a predetermined thickened portion 11. The soft magnetic alloy 1 of this embodiment can be applied to various magnetic components such as coil components such as inductors, filters, and antennas, and is particularly preferably applied to magnetic cores in coil components such as inductors. The magnetic core containing the soft magnetic alloy 1 may contain a resin component, or the magnetic core may be formed by mixing the soft magnetic alloy 1 with other magnetic particles.
[0075] (Summary of the embodiment) In the soft magnetic alloy 1 of this embodiment, a P-enriched region 11a having a specific characteristic is formed outside an internal region 2 having a soft magnetic alloy composition containing Fe and P. Such a characteristic can suppress rusting of the soft magnetic alloy 1 when it is submerged in water, and improve corrosion resistance. In particular, by making the P concentration in the P-enriched region 11a 1.5 or more (more preferably 2.0 or more), the corrosion resistance of the soft magnetic alloy 1 can be further improved.
[0076] Moreover, it is preferable that the concentrated portion 11 has a Co-enriched region 11b so as to overlap with the P-enriched region 11a, and the formation of the Co-enriched region 11b further improves the corrosion resistance of the soft magnetic alloy 1. In particular, by making the Co concentration in the Co-enriched region 11b exceed 1.20, the corrosion resistance of the soft magnetic alloy 1 can be further improved.
[0077] Moreover, by forming the concentrated portion 11 in the amorphous soft magnetic alloy 1 having a degree of amorphousness of 85% or more, the corrosion resistance of the soft magnetic alloy 1 can be further improved while ensuring a high saturation magnetic flux density Bs.
[0078] Although the embodiment of the present invention has been described above, the present invention is not limited to the above-mentioned embodiment, and various modifications can be made within the scope of the present invention. EXAMPLES
[0079] The present invention will be described in more detail below with reference to specific examples. However, the present invention is not limited to the following examples. In the table below, sample numbers marked with * are comparative examples.
[0080] Experiment 1 In experiment 1, soft magnetic alloy powder was produced by gas atomization. In gas atomization, the following conditions were set: molten metal injection temperature: 1500°C, molten metal injection rate: 1.2 kg / min, high pressure gas pressure: 7.0 MPa, cooling water pressure: 10 MPa, and soft magnetic alloy powder with a volume-based average particle size (D50) in the range of 15 to 30 μm was obtained. Then, the soft magnetic alloy powder was subjected to heat treatment under the conditions shown in Table 1 to obtain soft magnetic alloys according to samples 2 to 13. In addition, in experiment 1, a soft magnetic alloy according to sample 1, which was not subjected to heat treatment, was also produced, and the following evaluation was performed based on sample 1.
[0081] <Composition and crystal structure of soft magnetic alloy powder> The composition of the soft magnetic alloy powder obtained by the gas atomization method was measured by ICP. As a result, in all samples in Experiment 1, the soft magnetic alloy powder (i.e., inner region 2) had the composition formula: (Fe 0.7 Co 0.3 ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01 It was confirmed that the alloy composition satisfied the following criteria: (atomic ratio; α=0.300, β=0, γ=0, a=0.110, b=0.020, c=0.030, d=0.010, e=0.010). In addition, when X-ray crystal structure analysis was performed on the soft magnetic alloy powder of Experiment 1 by XRD, it was confirmed that the soft magnetic alloy powder (i.e., inner region 2) in all samples of Experiment 1 was amorphous with an amorphization degree X of 85% or more.
[0082] <Analysis of surface structure> For the soft magnetic alloys of each sample in Experiment 1, a thin slice sample was taken from the vicinity of the surface layer by a microsampling method using an FIB. Then, using the thin slice sample, a mapping analysis was performed by TEM-EDX to investigate the presence or absence of enriched portion 11 (P-enriched region 11a and Co-enriched region 11b). In addition, a component analysis was performed in a specific region by TEM-EELS to measure the degree of P enrichment and the degree of Co enrichment in enriched portion 11. The analysis results of the surface layer structure are shown in Table 1. The EELS analysis confirmed that enriched portion 11, including P-enriched region 11a and Co-enriched region 11b, was an amorphous metal phase.
[0083] <Saturation magnetic flux density Bs> The Bs of the soft magnetic alloys of each sample was measured using a vibrating sample magnetometer (VSM) under a magnetic field of 1000 kA / m. The measurement results are shown in Table 1. Regarding Bs, a value of 1.50 T or more was judged to be good, and a value of 1.70 T or more was judged to be even better.
[0084] <Water immersion test> First, before conducting the water immersion test, magnetic core samples were prepared using the soft magnetic alloys of each specimen. The magnetic core samples were prepared according to the following procedure. Granules were obtained by mixing 100 parts by mass of the soft magnetic alloy with 3 parts by mass of epoxy resin. The granules were then filled into a mold and subjected to a pressure of 4 ton / cm. 2 The magnetic core sample was pressed at a pressure of 1.0 mm to obtain a toroidal magnetic core sample having an outer diameter of 11 mm, an inner diameter of 6.5 mm, and a height of 1.0 mm.
[0085] A water immersion test was conducted to evaluate the corrosion resistance of the magnetic core samples obtained above. In the water immersion test, the magnetic core samples were immersed in tap water, and the time until rust was visually observed (rust onset time) was measured. In experiment 1, the rust onset time T1 of sample 1, which was not heat-treated, was used as the standard to evaluate the corrosion resistance of each sample. Specifically, in experiment 1, samples whose rust onset time was less than 1.0 times T1 (rust onset time of sample 1) were judged as "F (fail)", samples whose rust onset time was more than 1.0 times but less than 1.2 times T1 were judged as "G (good)", and samples whose rust onset time was 1.2 times or more T1 were judged as "VG (very good)". The results of the three-level evaluation based on the above "F, G, VG" are shown in Table 1.
[0086] [Table 1]
[0087] As shown in Table 1, it was confirmed that the P-enriched region 11a was formed in the samples 3 to 13 that were heat-treated under the specified conditions, and that the rust generation time was longer than that of the samples 1 and 2. In particular, it was confirmed that the Co-enriched region 11b was formed so as to overlap with the P-enriched region 11a in the samples 4 to 13 that were heat-treated at a gauge pressure higher than that of the sample 3, and the corrosion resistance was improved more than that of the sample 3. From these results, it was found that by forming the P-enriched region 11a on the surface side of the soft magnetic alloy, a high Bs can be ensured and the corrosion resistance relative to the reference alloy (sample 1) can be improved. It was also found that the corrosion resistance was further improved by forming the Co-enriched region 11b so as to overlap with the P-enriched region 11a.
[0088] In addition, in Table 1, specific values for the rust occurrence time are omitted, but it was confirmed that the higher the Co concentration, the longer the rust occurrence time compared to the standard sample 1, and the tendency for the relative corrosion resistance to be better.
[0089] Experiment 2 In experiment 2, the alloy composition was changed to obtain soft magnetic alloys according to samples 14 to 105. The alloy composition of each sample analyzed by ICP is shown in Tables 2 to 7.
[0090] Specifically, in samples 14 to 29 shown in Table 2, the composition formula: (Fe 1-α Co α ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01 While satisfying the following conditions (atomic ratios; β=0, γ=0, a=0.110, b=0.020, c=0.030, d=0.010, e=0.010), soft magnetic alloys were prepared by changing the atomic ratio α of Co. Sample 22 is the same as Sample 1 in Table 1, and Sample 23 is the same as Sample 11 in Table 1.
[0091] In addition, for samples 30 to 49 shown in Table 3, the atomic ratios of Co, Ni, and X1 were fixed at α = 0.300, β = 0, and γ = 0, and the atomic ratios of metalloids (B, P, Si, C) and Cr were changed to produce soft magnetic alloys.
[0092] In addition, in samples 50 to 53 shown in Table 4, the composition formula: (Fe (1-(0.3+β) Co 0.3 Ni β ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01 While satisfying the conditions (atomic ratios: α = 0.300, γ = 0, a = 0.110, b = 0.020, c = 0.030, d = 0.010, e = 0.010), soft magnetic alloys were prepared by changing the Ni atomic ratio β.
[0093] In addition, in samples 54 to 105 shown in Tables 5 to 7, the composition formula ((Fe 0.7 Co 0.3 ) 0.975 X1 0.025 ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01While satisfying the following conditions (atomic ratio: α = 0.300, β = 0, γ = 0.025, a = 0.110, b = 0.020, c = 0.030, d = 0.010, e = 0.010), a soft magnetic alloy was prepared by changing the element type of X1.
[0094] It was confirmed that the degree of amorphousness X of each soft magnetic alloy in Experiment 2 was 85% or more. In Experiment 2, samples with and without a prescribed heat treatment were prepared for each alloy composition, and in Tables 2 to 7, the samples with and without heat treatment are indicated as "Y" and "N", respectively. The heat treatment conditions in Experiment 2 were as follows: holding temperature: 200°C, holding time: 1 h, oxygen concentration in the heating furnace: 100 ppm, and gauge pressure in the heating furnace: 0.30 kPa.
[0095] In addition, for each of the samples 14 to 105 in the experiment 2, the measurement of Bs and the water immersion test were carried out in the same manner as in the experiment 1. In the water immersion test in the experiment 2, the rust formation time T N Based on the standard, the time to rust on the heat-treated sample was T Y As, T Y / T N Samples with a score of <1.0 were classified as "F (fail)" and those with a score of 1.0 ≤ T Y / T N Samples with a T < 1.2 were classified as "G (good)" and samples with a T < 1.2 were classified as "G (good)". Y / T N The samples that met the criteria were judged to be “VG (particularly good).” The evaluation results are shown in Tables 2 to 7.
[0096] [Table 2]
[0097] [Table 3]
[0098] [Table 4]
[0099] [Table 5]
[0100] [Table 6]
[0101] [Table 7]
[0102] As shown in Tables 2 to 7, the samples that underwent the specified heat treatment had higher corrosion resistance than the samples that did not undergo heat treatment. These results show that, within the range of the alloy composition shown in Experiment 2, by forming concentrated parts 11 with specified characteristics (P-enriched region 11a and Co-enriched region 11b), it is possible to improve corrosion resistance while maintaining a high Bs.
[0103] In addition, to add a supplement to the results in Table 2, the rust generation time tended to be longer as the Co content in the inner region 2 (i.e., the Co content of the soft magnetic alloy) increased. In other words, the corrosion resistance as an absolute evaluation increased as the Co content in the inner region 2 increased. However, as shown in sample 29 in Table 2, when the Co content in the inner region 2 was high, the Co enrichment degree tended to be warped and reduced. In addition, the relative corrosion resistance improvement effect (i.e., corrosion resistance relative to the reference alloy) was better in other samples 17, 19, 21, 23, 25, and 27, which had higher Co enrichments, than in sample 29. In other words, from this result, it was confirmed that the higher the Co enrichment degree, the greater the tendency for the corrosion resistance improvement effect relative to the reference alloy (a sample that was not subjected to heat treatment to form an enriched region) to be.
[0104] Experiment 3 In experiment 3, amorphous soft magnetic alloy powders with an amorphous degree X of 85% or more (samples 1 and 11), nanocrystalline soft magnetic alloy powders with an amorphous degree X of less than 85% (samples 106 and 107), and crystalline soft magnetic alloy powders with an amorphous degree X of less than 85% (samples 108 and 109) were produced to investigate the effect of differences in the crystal structure of the soft magnetic alloys on corrosion resistance.
[0105] In Experiment 3, the crystal structure of each sample was controlled by a pre-processing heat treatment. Specifically, in Samples 1 and 11 of Experiment 3, the pre-processing heat treatment was not performed, and thus amorphous soft magnetic alloy powder was obtained. In Samples 106 and 107 of Experiment 3, the pre-processing heat treatment was performed at a holding temperature of 500°C, and thus nanocrystalline soft magnetic alloy powder was obtained. In Samples 108 and 109 of Experiment 3, the pre-processing heat treatment was performed at a holding temperature of 650°C, and thus crystalline soft magnetic alloy powder was obtained. Other conditions in the above pre-processing heat treatment were a heating rate of 100°C / min, an atmosphere in the furnace: an Ar atmosphere, and a gauge pressure in the heating furnace: 0.0 kPa, and the crystal structure was controlled in a state in which the concentrated portion 11 was not formed.
[0106] The composition of the soft magnetic alloys in each sample in Experiment 3 was (Fe 0.7 Co 0.3 ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01 The same is true for all samples. In experiment 3, for each crystal structure, samples were prepared with and without heat treatment to form concentrated portion 11. In Table 8, the samples with heat treatment are indicated as "Y" and those without heat treatment are indicated as "N." In addition, for samples (107, 109) that were subjected to the pre-process heat treatment, the heat treatment to form concentrated portion 11 was performed after the pre-process heat treatment. The conditions for the heat treatment in experiment 3 were: holding temperature: 200°C, holding time: 1.0 h, oxygen concentration in the heating furnace: 100 ppm, and gauge pressure in the heating furnace: 0.3 kPa.
[0107] In Experiment 3, Bs measurement and water immersion test were performed in the same manner as in Experiment 2. In the water immersion test of Experiment 3, the rust generation time T N Based on the standard, the time to rust on the heat-treated sample was T Y As, T Y / T N Samples with a score of <1.0 were classified as "F (fail)" and those with a score of 1.0 ≤ T Y / T N Samples with a T < 1.2 were classified as "G (good)" and samples with a T < 1.2 were classified as "G (good)". Y / T N The samples that met the criteria were judged to be "VG (particularly good)." The evaluation results of Experiment 3 are shown in Table 8.
[0108] [Table 8]
[0109] As shown in Table 8, even in the case of nanocrystalline or crystalline soft magnetic alloys, as in the case of amorphous alloys, it was found that the corrosion resistance of samples 107 and 109 in which the P-enriched region 11a and the Co-enriched region 11b were formed by a predetermined heat treatment was improved compared to samples 106 and 108 which were not subjected to heat treatment. In addition, when the results of samples 106 to 109 shown in Table 8 are compared with the results of samples 1 and 11, it was found that when the soft magnetic alloy is amorphous, the rusting time is longer than that of the reference alloy, and the relative improvement effect of the corrosion resistance is particularly good.
[0110] Experiment 4 In experiment 4, ribbon-shaped soft magnetic alloy samples (samples 110 and 111) were produced by the single roll method. The ribbon production conditions were: temperature of molten metal sprayed onto the roll: 1300°C, roll temperature: 30°C, roll rotation speed: 25 m / sec. The atmosphere inside the chamber was air. The soft magnetic alloy ribbon obtained under the above conditions had a thickness of 20 to 25 μm, a width in the short direction of about 5 mm, and a ribbon length of about 10 m.
[0111] In addition, in experiment 4, the alloy compositions of samples 110 and 111 were measured by ICP in the same manner as in experiment 1. 0.7 Co 0.3 ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01 (Atomic ratio; α=0.300, β=0, γ=0, a=0.110, b=0.020, c=0.030, d=0.010, e=0.010) was satisfied. Furthermore, when the crystal structures of the soft magnetic alloy ribbons of Samples 110 and 111 were measured by XRD, it was confirmed that both were amorphous with an amorphization degree X of 85% or more.
[0112] The soft magnetic alloy ribbon of sample 110 was subjected to analysis of the surface layer structure, measurement of Bs, and water immersion test without heat treatment. On the other hand, the soft magnetic alloy ribbon of sample 111 was subjected to heat treatment under the conditions shown in Table 9, and then the same evaluation as that of sample 110 was performed. In the water immersion test of the soft magnetic alloy ribbon, a test sample was prepared by cutting the ribbon into an arbitrary size (length about 4 cm × width about 5 mm), and the ribbon-shaped test sample was immersed in tap water. The method of pass / fail judgment in experiment 4 was the same as that in experiment 1. The evaluation results of each sample in experiment 4 are shown in Table 9. In addition, Table 9 also shows the experimental results of soft magnetic alloy powders (samples 1 and 11 in experiment 1) having the same alloy composition as samples 110 and 111.
[0113] [Table 9]
[0114] As shown in Table 9, even when the soft magnetic alloy has a ribbon shape, it was confirmed that the corrosion resistance can be improved while maintaining a high Bs by forming the P-enriched regions 11a and the Co-enriched regions 11b by a predetermined heat treatment. [Explanation of symbols]
[0115] 1,1a,1b … Soft magnetic alloy 2 … Inner region 10 … Outermost surface 11 … Enrichment part 11a … P enrichment region 11b … Co enrichment region 12 … SB oxide layer 13 … Fe oxide layer 20 … Coating layer
Claims
1. an inner region having a soft magnetic alloy composition including Fe and P (phosphorus); A P-enriched region is present on the surface side of the internal region and has a higher P concentration than the internal region, The P concentration in the P-enriched region is 1.31 or more, The soft magnetic alloy has a P content in the inner region of 2.0 at% to 7.0 at%.
2. The P-enriched region is composed of elements common to the internal region, 2. The soft magnetic alloy according to claim 1, wherein the total content of elements in the P-enriched region and the internal region is 50% or more in terms of a substance amount ratio.
3. the inner region contains Co, A Co-enriched region is present on the surface side relative to the internal region, 3. The soft magnetic alloy according to claim 1, wherein the Co-enriched region overlaps at least a portion of the P-enriched region.
4. 4. The soft magnetic alloy according to claim 3, wherein the Co-enriched regions are metallic phases.
5. 5. The soft magnetic alloy according to claim 3, wherein the degree of Co enrichment in the Co-enriched region is greater than 1.
2.
6. 6. The soft magnetic alloy according to claim 1, wherein the P concentration in the P-enriched region is 1.5 or more.
7. 7. The soft magnetic alloy according to claim 1, wherein the P concentration in the P-enriched region is 2.0 or more.
8. 8. The soft magnetic alloy according to claim 1, wherein the degree of amorphousness is 85% or more.
9. The soft magnetic alloy according to any one of claims 1 to 8, which is in the form of a ribbon.
10. The soft magnetic alloy according to any one of claims 1 to 8, which is in the form of a powder.
11. A magnetic component comprising the soft magnetic alloy according to any one of claims 1 to 10.
Citation Information
Patent Citations
Hyperfine-crystal fe-base alloy excellent in corrosion resistance and its production
JP1989247555A
Fe-base amorphous alloy ribbon with extra thin oxide layer
JP2000313946A
Amorphous soft magnetic alloy, amorphous soft magnetic alloy member, amorphous soft magnetic alloy ribbon, amorphous soft magnetic alloy powder and magnetic core and inductance component using the same
JP2007231415A
Highly corrosion-resistant amorphous alloy
JP2009293099A
Amorphous alloy powder, dust core, magnetic element and electronic apparatus
JP2014167139A